Burnout among Croatian physicians: a cross-sectional national survey - Pintarić Japec, Vanja (Croat Med J, 2019)
AIM: To investigate the prevalence of burnout syndrome among physicians of all specialties, including residents and non-specialists, on a national level in Croatia. METHODS: This cross-sectional study, conducted in October 2017, used anonymous online survey based on the Maslach Burnout Inventory Human Services Survey. The Croatian version of the inventory was assessed for acceptability, factorial validity, and reliability. Key dimensions of burnout – emotional exhaustion, depersonalization, and lack of personal accomplishment were assessed. Respondents scoring high for emotional exhaustion or depersonalization were defined as burned-out. RESULTS: The response rate was 18% (2557/14 427). Respondents’ median age was 41 years (range 25-80), and 68% (1737/2557) were women. Good sampling adequacy and scale reliability were confirmed. Factorial validity suggested the presence of three overall factors, and no items were eliminated. Sixty-three percent of physicians were burned-out. High score on emotional exhaustion, depersonalization, and reduced personal accomplishment were found in 58%, 29%, and 52% of respondents, respectively. As many as 16% of the respondents simultaneously experienced high levels of all three burnout dimensions. Multivariate logistic regression analysis revealed that residents and physicians in tertiary or primary care were at an increased risk of burnout, while physicians working in institutes were at a decreased risk. CONCLUSION: Active national measures are needed to reduce the high prevalence of burnout among Croatian physicians.